Protective barrier for safety glass
Through the multi-layer PET membrane lens stacking and UV stabilizer design, the durability and safety issues of vehicle windshield are solved, and a high wear resistance and low cost windshield solution is achieved.
Patent Information
- Application Number
- CN202510833396.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-04
- Filing Date
- 2021-03-02
- Publication Date
- 2025-08-01
AI Technical Summary
The existing vehicle windshield has high replacement cost and insufficient durability, especially the plastic windshield is prone to wear and break when used externally. The glass windshield produces sharp debris when impacted. The existing membrane cannot meet the weather resistance and wear resistance requirements of ANSI Z26 standards.
Using a multi-layer polyethylene terephthalate (PET) film lens stack, including a hard coating and adhesive layer, optical performance is controlled by modulation transfer function, ensuring high contrast and wear resistance at high incidence angles, and improving weather resistance with UV stabilizers, the lens can be replaced as needed to extend service life.
It improves the wear and impact resistance of the windshield, reduces the risk of glass fragments, meets the durability requirements of the ANSI Z26 standard, reduces replacement frequency and cost, while maintaining good optical performance and service life.
Smart Images

Figure CN120396638A_ABST
Abstract
Description
[0001] This patent application is a divisional application of the patent application with application number 202180020242.5, filing date March 2, 2021, and invention title "Protective Barrier for Safety Glazing".
[0002] Cross - reference to related applications
[0003] This application claims the benefit of priority to U.S. Provisional Application No. 62 / 987,726, filed on March 10, 2020, with the title "PROTECTIVE BARRIER FOR SAFETY GLAZING", the entire content of which is hereby incorporated by reference in its entirety.
[0004] Statement: Federally sponsored research / development
[0005] Not applicable Technical field
[0006] The present disclosure generally relates to safety glazing, and more particularly, to a protective barrier applied to the exterior of a vehicle windshield. Background art
[0007] Currently, vehicle windshields are manufactured to include optoelectronic devices such as cameras, rain sensors, proximity sensors, head - up displays, defrosters, and antennas. This has increased the cost of replacing a broken windshield by a factor of 10. Additionally, expensive calibration procedures must be performed after installing a new windshield, which further increases the cost associated with replacing the windshield.
[0008] The American National Standards Institute (ANSI) Z26.1 - 1996 standard, entitled "Safety Glazing Materials for Glazing Motor Vehicles and Motor Vehicle Equipment Operating on Land Highways", is a standard that specifies the durability and safety requirements for qualified materials for vehicle glass. The various tests specified by the standard are transmittance, humidity, heating, impact, breakage, permeability, distortion, weathering, haze, and abrasion resistance. Applicable standards such as the Z26.1 - 1996 standard currently specify the construction of safety glazing for sixteen categories that can be in different positions in a vehicle. The most stringent category is the windshield, as visual acuity, impact resistance, resistance to pitting and wiper wear are required, and it is necessary to prevent glass fragments from flying to prevent them from injuring passengers.
[0009] The two basic construction materials for windshields are glass and plastic. According to applicable standards, plastic is only used for vehicles such as motorcycles, and the windshield is only allowed to be higher than the seat by 15 inches so that the rider can look over the windshield. This is because the currently available plastic is very soft, so that the plastic is prone to wear, and the visual acuity of the windshield will decrease after only a short service life. Considering their limited use, the abrasion test for plastic (for example, test 5.17 specified in ANSI Z26.1-1996 standard) only requires 100 Taber abrasion cycles. This is 1 / 10 of the requirement for glass, which is 1,000 Taber abrasion cycles. On the other hand, plastic can be a preferred material because plastic does not produce sharp fragments like glass when impacted, and the weight of plastic is half that of glass. Although glass is hard and wear-resistant, its low tensile strength makes it prone to pitting. In addition, upon impact, glass produces dangerous sharp fragments that can injure passengers. To mitigate this safety issue, glass windshields can be laminated with a soft plastic core to keep the fragments together and improve penetration resistance.
[0010] Commercially available safety barrier films for windshields do not yet meet the applicable requirements for one-year weather resistance (for example, test 5.16 specified in ANSI Z26.1-1996 standard), plastic wear (for example, test 5.17 specified in ANSI Z26.1-1996 standard), and glass wear (for example, test 5.18 specified in ANSI Z26.1-1996 standard). The applicable requirements are shown in the following table:
[0011]
[0012] In the current commercial market, existing polymer safety films for protecting glass windows are installed inside buildings or vehicles. If installed outside, due to the embrittlement of the polyester substrate, these commercially available products will not last more than a few months. Installing outside will cause the hard coating on the surface to crack, thus resulting in film failure. The durability of the safety film installed inside the window is specified in ANSI Z97.1-2015, "American National Standard for Safety Glazing Materials Used in Buildings—Safety Performance Specifications and Methods of Test". An example of such an internally installed safety film is the 3M Scotch-shield Safety and Security Window Film Ultra series, which has a thickness of 8 mils, a peel strength of 2,000 g / in, a transmittance greater than 88%, is substantially undeformed at an incident angle of 45 degrees, and has a wear resistance of 5% haze after 100 Taber cycles. Although the service life of this film can be 10 years, this film is not manufactured for external use, and the wear resistance does not meet the ANSI Z26 windshield use requirements (for example, haze less than 2% after 1,000 Taber cycles).
[0013] In the case of installing a safety film such as the 3M film described above inside, the glass window itself can provide protection against part of the UV and IR spectra. Adding UV inhibitors mixed into the installation adhesive may be sufficient to give the film and the surface of the hard coating facing the inside a long service life (for example, 10 years). However, due to the low tensile strength of the glass, the outer glass surface is still vulnerable to pitting.
[0014] The only commercially available safety film for external use on vehicles traveling on land roads is manufactured by Clear-Plex. According to the published product specifications of Clear-Plex and related U.S. Patent Nos. 7,992,917 and 9,023,162, the Clear-Plex safety film includes a 4-mil-thick PET layer, which has a hard coating and a pressure-sensitive adhesive for installation, and has a peel strength of 1,800 g / in, a transmittance greater than 87%, is substantially undeformed at an incident angle of 40 degrees, and has a wear resistance of 0.5% haze after 100 cycles before weathering. Clear-Plex does not claim any tests conducted against the ANSI Z26 standard. The haze value is acceptable for plastics, but the product specifications do not include the Taber test after 1 year of weathering.
[0015] There are other articles that can be installed outside the windshield of vehicles that do not travel on land roads, such as vehicles for racing or military use. One such article provided by Racing Optics, Inc. is a 4-layer × 4 mil safety film (hereinafter referred to as "RO 4×4"), which has a thickness of 18 mil (4 mil thick PET for 4 layers, where each layer has a hard coating and a pressure-sensitive adhesive), the peel strength of the upper layer is 100 g / in, and the peel strength of the base layer is 400 g / in, the transmittance is greater than 88%, the result of the Z26 haze test #5.17 before weathering is less than 1.5% haze, the result of the Z26 abrasion test #5.16 after 100 Taber cycles is less than 5% haze, and the result of the Z26 weather resistance test #5.15 for each layer is less than 4 months (for example, the transmittance decreases significantly after weathering for 3 to 4 months, so that the haze without Taber test is about 20% to 50%). Since the RO 4×4 article is designed for a short service life (it is updated as each layer peels off during use), this article does not have the weather resistance or abrasion resistance required to meet the Z26 standard for the windshields of vehicles traveling on land roads. SUMMARY OF THE INVENTION
[0016] The present disclosure contemplates various systems and methods for overcoming the disadvantages of the above related art. According to one or more aspects of the present disclosure, an external barrier can be added to both glass and plastic windshields to improve abrasion resistance, pitting resistance, and impact breakage resistance. The external barrier can enhance passenger safety and reduce the first insurance cost of the national fleet, i.e., windshield damage, while reducing the carbon footprint of replacing glass windshields.
[0017] One aspect of an embodiment of the present disclosure is a protective barrier attachable to a curved substrate. The protective barrier can include a stack of two or more lenses, each of the two or more lenses including a polyethylene terephthalate (PET) film, a hard coating on a first side of the PET film, and an adhesive layer on a second side of the PET film opposite the first side. The stack of two or more lenses can have a modulation transfer function that exhibits a contrast value greater than 75% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees.
[0018] The modulation transfer function of a stack of two or more lenses can exhibit a contrast value greater than 70% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 70 degrees. The modulation transfer function of a stack of two or more lenses can exhibit a contrast value greater than 85% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 55 degrees. The modulation transfer function of a stack of two or more lenses can exhibit a contrast value greater than 90% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 45 degrees.
[0019] The PET film of each of the two or more lenses can have a modulation transfer function that exhibits a contrast value greater than 80% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees.
[0020] Each of the two or more lenses can be 2 mil to 4 mil thick.
[0021] The PET film of each of the two or more lenses can include a UV stabilizer. The hard coat and adhesive layer of each of the two or more lenses can include a UV stabilizer.
[0022] The longitudinal shrinkage rate of the PET film of each of the two or more lenses can be 0.6% to 1.8% at 150 °C, and the transverse shrinkage rate can be 0.3% to 1.1%.
[0023] Another aspect of the embodiments of the present disclosure is a method. The method can include stacking two or more lenses, each of the two or more lenses including a polyethylene terephthalate (PET) film, a hard coat on a first side of the PET film, and an adhesive layer on a second side of the PET film opposite the first side. The stack of two or more lenses can have a modulation transfer function that exhibits a contrast value greater than 75% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees. The method can include placing the stack of two or more lenses on a curved substrate, where the adhesive of the first lens of the stack contacts the curved substrate, and applying heat and pressure to conform the stack of two or more lenses to the shape of the curved substrate.
[0024] Applying heat and pressure can be performed at least partially before the adhesive layer of each of the two or more lenses is fully cured. Applying heat and pressure can be performed at least partially before the peel strength of the adhesive layer of each of the two or more lenses exceeds 25 grams per inch of a constant load determined to be required for peeling.
[0025] The method can include peeling the outermost lens of the stack of two or more lenses after applying heat and pressure.
[0026] The adhesive of the first lens in the stack of two or more lenses is stronger than the adhesive of the outermost lens in the stack of two or more lenses.
[0027] The modulation transfer function of the stack of two or more lenses can exhibit a contrast value greater than 70% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 70 degrees.
[0028] Each of the two or more lenses may have a PET film with a modulation transfer function that exhibits a contrast value greater than 80% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees.
[0029] Each of the two or more lenses may be 2 mil to 4 mil thick.
[0030] The PET film of each of the two or more lenses may contain a UV stabilizer. The hard coat and adhesive layer of each of the two or more lenses may contain a UV stabilizer.
[0031] The longitudinal shrinkage rate of the PET film of each of the two or more lenses may be 0.6% to 1.8% at 150 °C, and the transverse shrinkage rate may be 0.3% to 1.1%. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above and other features and advantages of the various embodiments disclosed herein will be better understood by reference to the following description and drawings, in which like reference numerals always refer to like parts, and in which:
[0033] Figure 1 is a cross-sectional view of a protective barrier according to an embodiment of the present disclosure;
[0034] Figure 2 is an image and illustration of visual distortion in a security film;
[0035] Figure 3 is an illustration of modulation transfer function (MTF) data for five samples at different incident angles;
[0036] Figure 4 is an illustration of the windshield damage rate for different film thicknesses;
[0037] Figure 5 shows a protective barrier placed on the windshield of an automobile at the start of a process of applying heat and pressure to form the protective barrier into the shape of a windshield;
[0038] Figure 6 shows the protective barrier on the windshield at the end of the process of applying heat and pressure;
[0039] Figure 7 shows a protective barrier after being trimmed to fit a windshield; and
[0040] Figure 8 is an exemplary operation flow according to an embodiment of the present disclosure. DETAILED DESCRIPTION
[0041] The present disclosure includes various embodiments of a protective barrier attachable to a curved substrate and methods of manufacturing, installing, and using the same. The detailed description presented below in conjunction with the accompanying drawings is intended as a description of several currently contemplated embodiments and is not intended to represent the only form in which the disclosed invention may be developed or utilized. The specification sets forth the functions and features in connection with the recited embodiments. However, it should be understood that the same or equivalent functions may be achieved by other embodiments that are also within the scope of the present disclosure. It should also be understood that relational terms such as first and second are used only to distinguish one entity from another entity and do not necessarily require or imply any actual such relationship between these entities.
[0042] Figure 1 is a cross-sectional view of a protective barrier 100 according to an embodiment of the present disclosure. The protective barrier 100 may be attachable to a curved substrate 10 such as an automotive windshield and may include a stack of two or more lenses 110, such as Figure 1 the lenses 110a, 110b, 110c shown. Each lens 110 may include a polyethylene terephthalate (PET) film 112, a hard coat 114 on a first side of the PET film 112, and an adhesive layer 116 on a second side of the PET film 112 opposite the first side, the adhesive layer 116 being for bonding the lenses 110 together and to the curved substrate 10. The stack of lenses 110 may have a modulation transfer function at an incident angle of 65 degrees that exhibits a contrast value greater than 75% for a spatial resolution of one line pair per 0.0003 radians, which is an approximate resolution of the human eye. By controlling the modulation transfer function of the stack of lenses 110 in this manner, a protective barrier 100 can be produced that is substantially non-deforming (e.g., less than 0.00045 radians displacement) when viewed at a typical incident angle (e.g., 60 degrees to 70 degrees) of an automotive windshield, even when the total thickness of the protective barrier 100 is sufficient to withstand impact damage at automotive speeds. In this way, the protective barrier 100 can prevent breakage and pitting of the underlying windshield 10 while meeting the durability requirements for use of a windshield on a highway.
[0043] Distortion is a visual acuity error caused by a displaced object in the far field (e.g., 40 feet to 1,000 feet). Safety glass can have local regions that cause displacement of an object that is perceived as distortion, where the object will appear to jump from one position to another when viewed from slightly different positions or angles. Typically, distortion is only qualitatively determined, for example, by Test 5.15 specified in ANSI Z26.1-1996 standard. This test uses a shadowgraph in a long channel with a collimated light source and a white screen. The technician places the specimen in the optical path at a perpendicular angle of incidence, 15 inches from the screen. Then, the technician looks for dark and bright artifacts caused by distortion. This test has no quantitative standard and does not address distortion at high angles of incidence (e.g., 60 degrees to 70 degrees) used in modern automotive windshields.
[0044] Ideally, distortion should be minimized to the resolution of a 20 / 20 eye, which is approximately one line pair per 0.0003 radians. For example, when an object is displaced by 0.0006 radians, the eye will perceive the change in position as distortion. Thus, distortion must be effectively reduced such that any object displacement is below the resolving power of the human eye and is thus considered distortion-free. At the same time, when observing safety glass at high angles of incidence (e.g., 60 degrees to 70 degrees), according to Snell's law, the optical thickness increases as a cosine function of the angle. This can cause any distortion effects to be amplified, especially for safety films with a thickness greater than about 4 mils that may be required for impact damage resistance at automotive speeds.
[0045] Figure 2 Images and illustrations of visual distortion in safety film 210. To quantitatively determine distortion, it can be expected that the modulation transfer function of a test material such as safety film 210 can be evaluated at a fixed spatial frequency of 0.0003 radians, which corresponds to the resolution of a 20 / 20 eye. To this end, as shown in the upper part of Figure 2 , an image of test pattern 220 can be captured through film 210 at the desired angle of incidence (e.g., Figure 2 65 degrees of Figure 2 , where test pattern 220 is, for example, a checkerboard pattern or target line pairs spaced 0.0003 radians apart. The lower part of
[0046] shows the corresponding modulation transfer function data, where for a given cross-section of data representing a single horizontal slice of the image, the contrast is represented as a function of the horizontal position. It can be seen that in the region of test pattern 220 observed through film 210, the modulation transfer function data exhibits a decrease in contrast, which corresponds to distorted line pairs. In some places, the modulation transfer function data exhibits such low contrast that the image is completely lost.
[0046] Such as Figure 2The test apparatus can be used to evaluate materials and processing parameters for manufacturing the protective barrier 100 described herein. In particular, by using such a test apparatus and / or test results derived therefrom, appropriate materials and processing parameters can be selected and / or adjusted to control the modulation transfer function of the stack of lenses 110 at one or more desired angles of incidence. In this regard, it is contemplated that the modulation transfer function of the stack of lenses 110 can be controlled in accordance with the method described in the commonly owned U.S. Provisional Application No. 62 / 942,943, filed on December 3, 2019, entitled "METHOD AND APPARATUS FOR REDUCING NON-NORMAL INCIDENCE DISTORTION IN GLAZING FILMS", the entire content of which is expressly incorporated herein by reference.
[0047] For example, at any or all stages of manufacturing the stack of lenses 110 (e.g., during the process of forming a PET film 112 by melting a resin, extruding the molten resin through a die to form a film, and cooling the film; during the process of applying a hard coat 114; during the process of applying an adhesive layer 116; etc.), one or more images of a test pattern 220 can be captured through the lens 110 or stack of lenses 110 being manufactured. For example, the images can be captured by aligning an image capture device at one or more desired angles of incidence through a roll-to-roll processing web including the lens 110 or stack of lenses 110. Based on such images, a computer can calculate MTF data and generate an output for adjusting processing parameters found to affect the modulation transfer function of the lens 110 or stack of lenses 110, such as the temperature setting of a heater used in melting the resin (e.g., the absolute or relative temperature of the gradient or distribution of multiple heating zones of an extruder assembly), the rotational speed of an extrusion screw (which can determine the melting time of the resin and the degree of mixing), the rotational speed of one or more rollers (which can determine the cooling time and / or the degree of force applied to the polymer film during cooling), the flow rate of the hard coat 114 or the adhesive layer 116, the deposition rate or other application rate, and / or the speed of stacking the lenses 110. For example, it can be expected that in some cases, the PET film 112 can be pre-manufactured and selected based on known MTF data of the PET film 112, while the modulation transfer function of the stack of lenses 110 can be actively controlled during the application of the hard coat 114 and / or the adhesive layer 116 and during the stacking of the lenses 110. In other cases, the PET film 112 can also be manufactured while actively controlling its modulation transfer function. The output of the computer can include, for example, a feedback signal for automatically adjusting the relevant processing parameters in either continuous processing or batch processing without user input. As another example, the output can include a visual representation of data to be interpreted by an operator, who will manually make the necessary adjustments.
[0048] Figure 3 Graphical representation of modulation transfer function data for five samples at different angles of incidence. To generate Figure 3 exemplary data, the modulation transfer function data as described Figure 2 can be obtained at 10-degree increments of the angle of incidence from the normal (zero degrees) to 70 degrees. It can be expected that the data can be normalized based on the modulation transfer function values of a windshield without any protective barrier. Since many automotive windshields are installed at a 65-degree tilt, additional data can be captured at 65 degrees or any other particular target angle similarly. As Figure 3As shown by the solid line with triangular data points, a sample labeled T-11 3×3 can be a stack of lenses 110 of the protective barrier 100 described herein, which has a modulation transfer function that exhibits a contrast value greater than 75% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees. As described above, 65 degrees is a typical windshield tilt. However, a driver must also observe objects above or below eye level, such that minimizing distortion at greater or lesser incident angles can also be advantageous. To this end, as shown by the example of the sample labeled T-113×3, for the same spatial resolution of one line pair per 0.0003 radians, the modulation transfer function of the stack of lenses 110 can also exhibit a contrast value greater than 70% at an incident angle of 70 degrees, a contrast value greater than 85% at an incident angle of 55 degrees, and / or a contrast value greater than 90% at an incident angle of 45 degrees. The protective barrier 100, which controls its modulation transfer function in this way, can be applied to a typical automotive windshield without distorting the position of the objects observed by the driver.
[0049] An example of a prefabricated PET film 112 that can be selected for the stack of lenses 110 based on known MTF data of the PET film 112 is a PET film 112 having the following modulation transfer function: the modulation transfer function itself exhibits a contrast value greater than 80% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees. One such material is a film sold by DuPont Teijin Films under the name 454, which is represented by the solid line with circular data points in Figure 3 The dashed line with diamond data points represents a sample of the lens 110 fabricated using this film as its PET film 112, where a hard coat 114 and an adhesive layer 116 are applied under the MTF control as described above. That is, during the processing of applying the hard coat 114 and the adhesive layer 116, one or more processing parameters (either in continuous or batch processing) are selected or adjusted to control the modulation transfer function at one or more incident angles. For example, to maintain a contrast value greater than 75% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees. It can be seen that the MTF data of this sample, which represents only a single lens 110 according to the subject matter of the present disclosure, is substantially similar to the MTF data of the sample labeled T-11 3×3 representing the entire protective barrier 100 including such a stack of lenses 110, although the thickness of the stack has increased. This can be achieved by stacking the lenses 110 under the MTF control as described above.
[0050] In contrast, in Figure 3The sample marked T-8 3×3, represented by a dotted line with square data points, was produced without MTF control. Although it is a 3-layer stack of a similar structure, its optical properties at high incident angles commonly used in automotive windshields are significantly worse. For example, as Figure 3 shown, the contrast value at an incident angle of 65 degrees is less than 60%. Such a product can only be used in applications with an incident angle less than 60 degrees, where the contrast value remains greater than 75%. The sample marked RO 4×4, represented by a solid line with circular data points and corresponding to the above-mentioned RO 4×4 product, is a 4-layer stack similarly produced without MTF control. This product exhibits even worse MTF data at relevant incident angles and can actually only be used in applications with an incident angle less than 50 degrees, after which the contrast value drops below 75%. It has been found that deformation can become apparent when the contrast value is less than 75%.
[0051] Figure 4 It is a diagram of the windshield damage rate for different film thicknesses. Figure 4 The exemplary data is based on the results of glass breakage studies on U.S. military glass conducted by the O’Gara-Hess Armor Company. Increasingly thick PET layers were installed on bulletproof glass, and three-quarter-inch steel balls were thrown at the glass at different speeds. The data shows the minimum speed that caused the glass to break for each PET film thickness. According to Figure 4 the data shown, the protective barrier 100 described herein should be 8 mil thick or thicker to protect the glass windshield at normal driving speeds of 45 mph to 65 mph, for example, 8 mil to 16 mil thick, and preferably 10 mil to 16 mil thick. For example, the protective barrier 100 can include 2 to 4 lenses 110 (e.g., 3 lenses 110a, 110b, and 110c as Figure 1 shown), where each lens 110 is 4 mil thick.
[0052] Typically, the increased thickness required to protect a glass windshield poses several challenges to the manufacture of the protective barrier 100. As described above, for example, the increased thickness magnifies distortion at large angles of incidence (e.g., 60 degrees to 70 degrees). This challenge can be overcome by controlling the modulation transfer function of the protective barrier 100 as described above, e.g., by producing a stack of lenses 110 having a modulation transfer function that exhibits a contrast value of greater than 75% at a spatial resolution of one line pair per 0.0003 radians at an angle of incidence of 65 degrees. Other challenges caused by the thickness of the protective barrier 100 include manufacturing an article that can be successfully molded onto a curved substrate 10 (e.g., an automotive windshield) to achieve a high degree of weather and abrasion resistance, as well as reduced haze, and maintain a reasonably long service life. Each of these challenges can be overcome by the disclosed protective barrier 100 described in more detail below.
[0053] Figure 5 Shown is the protective barrier 100 placed on the windshield 10 of the vehicle 20 at the beginning of the process of applying heat and pressure to mold the protective barrier 100 into the shape of the windshield 10 (the windshield 10 being the Figure 1 substrate 10 shown). The protective barrier 100 can be adhered to the windshield 10 by placing the adhesive layer 116 of the first (bottommost) lens 110a of the stack in contact with the windshield 10 (see Figure 1 ). The adhesive layer 116 of the first lens 110a can be, for example, a dry mounting adhesive disclosed in U.S. Patent No. 9,295,297 to Wilson, issued March 29, 2016, entitled "Adhesive Mountable Stack of Removable Layers," the entire contents of which are expressly incorporated herein by reference. Alternatively, a wet mounting adhesive, such as that disclosed in U.S. Patent No. 9,128,545 to Wilson, issued September 8, 2015, entitled "Touch Screen Shield," can be used, the entire contents of which are expressly incorporated herein by reference. The adhesive can be an acrylic adhesive, such as an acrylic pressure sensitive adhesive (PSA).
[0054] Most automotive windshields exhibit compound curvature such that protective barrier 100 will not conform to windshield 10 without shrinking at the upper and lower corners. Since protective barrier 100 can be flat (e.g., already manufactured in roll-to-roll processing), the stack of two or more lenses 110 will initially not conform to the curved shape of windshield 10, creating more or less adhesive areas and air pockets / bubbles between the stack of lenses 110 and the windshield. Thus, to conform the stack of lenses 110 to the shape of windshield 10, heat and pressure can be applied using a heater 30 such as a hot air source (e.g., a heat gun or a hair dryer) or an infrared heater. At the same time, pressure can be applied to the stack of lenses 110 using a card or a squeegee. In some cases, a sacrificial layer can be used as a female mold cavity to apply protective barrier 100 with the stack of lenses 110 being between the sacrificial layer and windshield 10, as described in commonly owned U.S. Application No. 16 / 778,928, filed on January 31, 2020, and titled “THERMOFORM WINDSHIELD STACK WITH INTEGRATED FORMABLE MOLD”, the entire content of which is expressly incorporated herein by reference.
[0055] When the installer heats and presses down on the stack of lenses 110, the stack of lenses 110 can shrink and stretch to assume the profile of the curved substrate 10 (windshield). In the case of a commercially available film with a thickness of only 2 mil, the necessary shrinkage can be easily achieved. On the other hand, a single-piece film that is 8 mil or thicker will wrinkle before the film conforms to the windshield, rendering it unusable. Given this challenge, protective barrier 100 described herein uses a plurality of thin lenses 110 (e.g., each 2 mil to 4 mil thick) that shrink well individually. The adhesive layer 116 between the stacked lenses 110 can be only partially cured to produce a very low peel strength (e.g., 15 g / in to 25 g / in) and high elasticity, and the adhesive layer 116 can be, for example, the same acrylic adhesive. In this way, the relationship of the individual stacked lenses 110 is such that they can “float” relative to each other such that shrinkage occurs without wrinkling any of the lenses 110. Once protective barrier 100 is installed and exposed to sunlight, for example, the adhesive layer 116 will cure and increase the peel and bond strength (e.g., 3 to 5 times), thus contributing to a long service life. For example, the peel strength after initial weathering can be 100 g / in to 150 g / in.
[0056] Figure 6Shows the protective barrier 100 on the windshield 10 at the end of the process of applying heat and pressure. At this stage, the required shrinkage has occurred, and the stack of lenses 110 of the protective barrier 100 has been formed into the curved shape of the windshield 10 without air cavities / bubbles. The technical specifications of the PET film include two shrinkage axes with different values, called the machine direction ("MD") and the transverse direction ("TD"). The machine direction refers to the direction of the web in the roll-to-roll processing used to manufacture the PET film, while the transverse direction refers to the direction across the roll direction. It is expected that the longitudinal shrinkage of the PET film 112 of the stack of the protective barrier 100 at 150 °C can be 0.6% to 1.8% (preferably 0.8% to 1.0%), and the transverse shrinkage can be 0.3% to 1.1% (preferably 0.5% to 0.6%). A PET film with a longitudinal shrinkage below 0.6% or a transverse shrinkage below 0.3% will not have sufficient shrinkage to conform to the windshield. On the other hand, when the shrinkage is too high, for example, greater than 1.8% in the longitudinal direction or greater than 1.1% in the transverse direction, it will be difficult for the installer to control the shrinkage in a manual operation procedure (e.g., using the heater 30 as described above).
[0057] Figure 7 Shows the protective barrier 100 including the stack of lenses 110 after the stack of the transparent lenses 110 has been trimmed to fit the windshield 10. A knife such as a utility knife or a craft knife with a stainless steel blade (a carbon blade may damage the windshield 10) can be used to trim the stack of lenses 110. The resulting trimmed stack of lenses 110 can be effectively invisible because it matches the shape of the underlying windshield 10 (although it may change the color of the windshield, as in the case of window tinting).
[0058] In addition to improving the moldability as described above, using multiple thin lenses 110 (e.g., 2 mil to 4 mil thick) instead of a single monolithic film can cause the haze to drop sufficiently to be used for automotive windshields. Generally, the haze of the PET film has two components: the scattering of incident light at the surface and the dispersion of incident light in the matrix material. The matrix component of the dispersion of incident light in the matrix material increases with the thickness of the PET film. For example, as shown in the following table:
[0059] Thickness Haze % 2 mil 0.4 4 mil 0.6 7 mil 0.8 10 mil 1.2
[0060] However, when multiple PET films are stacked, the effect does not accumulate, and the three layers together only increase the haze by about 0.1% to 0.2%. At the same time, the surface component of the haze is reduced by adding a hard coat or an adhesive. By constructing the protective barrier 100 to include a stack of lenses 110 with relatively thin PET films 112 instead of a single large PET film, a reduced haze can be achieved even though, as described above, the protective barrier 100 can be thick enough to withstand impacts at automotive speeds (e.g., 8 mil or thicker). In particular, the protective barrier 100 described herein includes a stack of two or more lenses 110, each lens including a PET film 112 with a hard coat 114 and an adhesive layer 116, which can achieve an initial (pre-weathered) haze of less than 1% (preferably less than 0.6%), making it suitable for automotive windshields.
[0061] Exposure to ultraviolet radiation at about 300 MJ / m 2 for one year according to a standard such as the ANSI Z26.1 - 1996 standard defines weathering (e.g., 301 MJ / m 2 or 306 MJ / m 2 , or 280 MJ / m 2 extrapolated based on 70 MJ / m every three months 2 ). To simulate exposure for one year in the outdoor climate of Arizona (Arizona was chosen as the weathering benchmark due to its high temperature and high-intensity sunlight), a natural sunlight concentrator can be used, such as a natural sunlight concentrator that complies with the American Society for Testing and Materials (ASTM) G90 standard entitled "Standard Practice for Performing Accelerated Outdoor Weathering of Materials Using Concentrated Natural Sunlight". The haze and abrasion resistance of the protective barrier 100 can be measured before and at the end of the exposure cycle.
[0062] In the comparative example of the above-described RO 4×4 article, a UV stabilizer such as a UV-absorbing compound was mixed into the hard coat and adhesive in each of the four layers. After only six months of exposure in Arizona, the outermost layer became unusable due to transmission loss, increased haze, and loss of hardness. Because there were so many UV inhibitors in the hard coat, the hard coat had reduced hardness and was damaged, causing the underlying PET core of the outermost layer to turn yellow and brittle. The resulting haze could exceed 20%.
[0063] Compared with RO 4×4 products, the protective barrier 100 described herein can be manufactured from the PET film 112 of each of two or more lenses 110 containing UV stabilizers such as hydroxyphenyl-benzotriazole or hydroxyphenyl-triazine UV absorbers. The hard coat 114 and / or the adhesive layer 116 of each lens 110 may also contain UV stabilizers. Since the UV stabilizer is incorporated into the PET film 112, a reduced amount of UV stabilizer can be used in the hard coat 114 and the adhesive layer 116, enabling the hard coat 114 to maintain its hardness without sacrificing UV stability. Dispensing the UV stabilizer over all components enables it to have high weather resistance during assembly, such that in the Arizona sun, the protective barrier 100 can exceed one year in ANSI G90 exposure and can look very good, with low haze, and little yellowing even after weathering. The abrasion resistance of the protective barrier 100 after 1,000 Taber cycles can be, for example, less than 1% haze before weathering and less than 4% (preferably less than 2%) haze after weathering.
[0064] Although the protective barrier 100 can have sufficient weather resistance, the outermost lens 110 (e.g., Figure 1 lens 110c in the 3-layer example of Figure 1 ) will eventually be damaged. When the outermost lens 110 deteriorates unacceptably over time (e.g., due to debris, oxidation, etc.) during the service life of a vehicle windshield or other window, the outermost lens 110 can simply be peeled off and removed, thereby exposing the underlying new lens 110. To this end, the adhesive layer 116 of the innermost lens 110a (see
[0065] Figure 8 can be stronger than the adhesive layer 116 used for the other lenses 110 (and in some cases, the adhesive layer 116 can have a further reduced strength with each additional lens 110). In this way, the innermost lens 110a can remain adhered to the windshield or other curved substrate 10 while peeling off another lens 110. For example, it can be expected that during the service life of the protective barrier 100, the innermost lens 110a can be intended to remain on the curved substrate 10, where additional lenses 110 can be removed as needed. Along the same lines, each such additional lens 110 beyond the first lens 110a can be provided with a tab or other means for easy peeling during the service life of the protective barrier 100. By peeling off the outermost lens 110 of the stack of lenses 110 in this way, the service life of the protective barrier 100 can be extended. Figure 8 is an exemplary operating procedure according to an embodiment of the present disclosure. Figure 1Exemplary method of the stacked protective barrier 100 of the lens 110 shown. The operation process may start with providing a PET film 112 to be used as the core of each of two or more lenses 110 (step 810). As described above, the PET film 112 of each lens 110 can be selected according to specific MTF data, such as a contrast value greater than 80% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees, and the PET film 112 of each lens 110 can be (for example) a film sold by DuPont Teijin Films under the name 454. Alternatively, the PET film 112 of each lens 110 can be manufactured while actively monitoring the MTF data in continuous processing or batch processing as described above. At this point, providing the PET film 112 can include (for example) melting the resin, extruding the molten resin through a die to manufacture a polymer film, and cooling the polymer film. A hard coat 114 can be deposited on the first side of the PET film 112 (step 820), preferably by wet deposition, but can be applied according to any suitable method including spin coating, dip coating, or vacuum deposition. Before or after applying the hard coat 114, the PET film 112 can be coated with an adhesive 116 on the opposite side (step 830). The three elements of the PET film 112, the hard coat 114, and the adhesive 116 can constitute one lens 110 described herein, which can be stacked to manufacture the protective barrier 100 (step 840).
[0066] During any or all of steps 810 to 840, the operation process can include controlling the MTF of the stack of lenses 110 (step 850). For example, the MTF of the stack of lenses 110 can be controlled so as to exhibit a contrast value greater than 75% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees. As explained above, this control can be achieved by selecting an appropriate pre-manufactured PET film 112 in step 810. Alternatively or additionally, the control of the MTF can be achieved by actively monitoring and adjusting the processing parameters (such as the roll speed of roll-to-roll processing, etc.) while manufacturing the PET film 112 in step 810, depositing the hard coat 114 in step 820, applying the adhesive layer 116 in step 830, and / or stacking two or more lenses 110 in step 840. It is contemplated that such actively monitored and adjusted processing parameters can include continuous processing and / or batch processing, where continuous processing includes a feedback loop for monitoring MTF data and batch processing has MTF determination results manually or automatically fed back from the previous batch.
[0067] Once the protective barrier 100 including the stack of lenses 110 has been assembled, the operation process can continue by installing the protective barrier 100 onto a curved substrate 10, such as Figures 5 to 7The windshield of the vehicle 20 shown. As described above, it can be installed while the adhesive layer 116 is only partially cured so that the plurality of lenses 110 "float" on the adhesive and are individually shaped to the shape of the substrate 10, rather than as a monolithic structure, to avoid wrinkling. Refer to Figure 8 For the operation process, a protective barrier 100 including a stack of lenses 110 can be placed on the windshield or other curved substrate 10 (step 860), where the adhesive layer 116 of the lowermost lens 110a (see Figure 1 ) contacts the curved substrate 10. For easier installation, the protective barrier 100 can be roughly cut (e.g., using an electric film cutter) so that it does not extend too far beyond the windshield 10. As Figure 5 and Figure 6 described, the operation process can continue to apply heat and pressure to conform the stack of two or more lenses 110 to the shape of the curved substrate 10 (step 870). In particular, the application of heat and pressure can be carried out at least partially before the respective adhesive layers 116 of the two or more lenses 110 are fully cured, for example, before the peel strength of the adhesive layer 116 exceeds 25 grams per inch of a constant load per unit width determined to be required for peeling. Before the adhesive layer 116 is fully cured, the protective barrier 100 can conform to the shape of the curved substrate 10.
[0068] After cooling the protective barrier 100, the installation can terminate with the final trimming as described in Figure 7 . Now, the protective barrier 100 including the stack of lenses 110 is uniformly formed and fixed to the windshield surface. By installing the protective barrier 100 in this way, chipping and abrasion damage to the windshield 10 can be reduced while still meeting the applicable standards for windshield transmittance, abrasion resistance, haze, and distortion of vehicles traveling on land roads.
[0069] As described above, it can be expected that the outermost lens 110 of the protective barrier 100 having more than one lens 110 can be peeled off and removed, thus exposing the unused surface of the underlying lens 110. In this regard, during the service life of the protective barrier 100 that has been installed on the vehicle 20, the operation process of Figure 8 can continue. When the outermost lens 110 becomes unacceptably deteriorated over time (e.g., after six months, after one year, after scratches caused by the wiper start to appear, etc.), the outermost lens 110 can be peeled off to expose the underlying next lens 110 (step 880). The timing of peeling off the outermost lens 110 can depend on the specific climate in which the protective barrier 100 is used. For example, some climates must be more exposed to the sun, while other climates require more frequent use of the wiper.
[0070] The foregoing description is given by way of example and not of limitation. From the above disclosure, those skilled in the art can devise variations within the scope and spirit of the invention disclosed herein. Additionally, the various features of the embodiments disclosed herein can be used singly or in combination with each other, and are not intended to be limited to the specific combinations described herein. Thus, the scope of the claims is not limited by the embodiments shown.
Claims
1. A protective barrier attachable to a curved substrate, the protective barrier comprising a stack of two or more lenses, each of the two or more lenses comprising a plastic film and a hard coating on a first side of the plastic film, the stack of the two or more lenses having a modulation transfer function that exhibits a contrast value greater than 75% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees.
2. The protective barrier according to claim 1, wherein the plastic film of each of the two or more lenses comprises polyethylene terephthalate (PET).
3. The protective barrier according to claim 1, wherein each of the two or more lenses is 2 mil to 4 mil thick.
4. A method for applying a protective barrier to a curved substrate, comprising: stacking two or more lenses, each of the two or more lenses comprising a plastic film and a hard coating on a first side of the plastic film, the stack of the two or more lenses having a modulation transfer function that exhibits a contrast value greater than 75% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 65 degrees; placing the stack of the two or more lenses on the curved substrate to contact the curved substrate; and applying heat and pressure to conform the stack of the two or more lenses to the shape of the curved substrate.
5. The method according to claim 4, wherein the plastic film of each of the two or more lenses comprises polyethylene terephthalate (PET).
6. A protective barrier attachable to a curved substrate, the protective barrier comprising a stack of two or more lenses, each of the two or more lenses comprising a plastic film and a hard coating on a first side of the plastic film, the stack of the two or more lenses having a modulation transfer function that exhibits a contrast value greater than 70% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 70 degrees.
7. The protective barrier according to claim 6, wherein the plastic film of each of the two or more lenses comprises polyethylene terephthalate (PET).
8. The protective barrier according to claim 6, wherein each of the two or more lenses is 2 mil to 4 mil thick.
9. A method for applying a protective barrier to a curved substrate, comprising: stacking two or more lenses, each of the two or more lenses comprising a plastic film and a hard coating on a first side of the plastic film, the stack of the two or more lenses having a modulation transfer function that exhibits a contrast value greater than 70% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 70 degrees; placing the stack of the two or more lenses on the curved substrate to contact the curved substrate; and applying heat and pressure to conform the stack of the two or more lenses to the shape of the curved substrate.
10. The method according to claim 9, wherein the plastic film of each of the two or more lenses comprises polyethylene terephthalate (PET).
11. A protective barrier attachable to a curved substrate, the protective barrier comprising a stack of two or more lenses, each of the two or more lenses comprising a plastic film and a hard coating on a first side of the plastic film, the stack of the two or more lenses having a modulation transfer function that exhibits a contrast value greater than 85% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 55 degrees.
12. The protective barrier according to claim 11, wherein the plastic film of each of the two or more lenses comprises polyethylene terephthalate (PET).
13. The protective barrier according to claim 11, wherein each of the two or more lenses is 2 mil to 4 mil thick.
14. A method for applying a protective barrier to a curved substrate, comprising: stacking two or more lenses, each of the two or more lenses comprising a plastic film and a hard coating on a first side of the plastic film, the stack of the two or more lenses having a modulation transfer function that exhibits a contrast value greater than 85% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 55 degrees; placing the stack of the two or more lenses on the curved substrate to contact the curved substrate; and applying heat and pressure to conform the stack of the two or more lenses to the shape of the curved substrate.
15. The method according to claim 14, wherein the plastic film of each of the two or more lenses comprises polyethylene terephthalate (PET).
16. A protective barrier attachable to a curved substrate, the protective barrier comprising a stack of two or more lenses, each of the two or more lenses comprising a plastic film and a hard coating on a first side of the plastic film, the stack of the two or more lenses having a modulation transfer function that exhibits a contrast value greater than 90% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 45 degrees.
17. The protective barrier according to claim 16, wherein the plastic film of each of the two or more lenses comprises polyethylene terephthalate (PET).
18. The protective barrier according to claim 16, wherein each of the two or more lenses is 2 mil to 4 mil thick.
19. A method for applying a protective barrier to a curved substrate, comprising: stacking two or more lenses, each of the two or more lenses comprising a plastic film and a hard coating on a first side of the plastic film, the stack of the two or more lenses having a modulation transfer function that exhibits a contrast value greater than 90% for a spatial resolution of one line pair per 0.0003 radians at an incident angle of 45 degrees; placing the stack of the two or more lenses on the curved substrate to contact the curved substrate; and Heat and pressure are applied to conform the stack of the two or more lenses to the shape of the curved substrate.
20. The method according to claim 19, wherein the plastic film of each of the two or more lenses comprises polyethylene terephthalate (PET).
Citation Information
Patent Citations
Thermoform windshield stack with integrated formable mold
US20200247102A1
Protective laminates for windshields
US7992917B2
Method of manufacturing a windshield having a protective laminate
US9023162B2
Touch screen shield
US9128545B2
Adhesive mountable stack of removable layers
US9295297B2